2014
DOI: 10.1080/20421338.2014.924264
|View full text |Cite
|
Sign up to set email alerts
|

Communication and quality service delivery in Uganda's local government: the mediating influence of total quality management

Abstract: The study aimed at understanding the role of total quality management (TQM) as a mediator between communication and quality service delivery (QSD) in Uganda's local government (LGs). Data were collected using a cross-sectional research design from 212 LGs whose heads of department and section heads formed the unit of inquiry. The paper utilises the Med Graph program, Sobel's z-test and the Kenny and Baron procedure to test the role of TQM as a mediator between communication and QSD. The findings revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Moreover, for information to meet its purpose, it must be communicated to the intended persons (Long and Jeremy, 2013). As communication is enhanced, there is a possibility that service quality will improve as organizations become more focused on clients requirements and needs (Musenze et al, 2014;Mwazo et al, 2017). This positions communication as a unique predictor to QSD (Musenze et al, 2013;Mwazo et al, 2017).…”
Section: Internal Control and Quality Service Delivery In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for information to meet its purpose, it must be communicated to the intended persons (Long and Jeremy, 2013). As communication is enhanced, there is a possibility that service quality will improve as organizations become more focused on clients requirements and needs (Musenze et al, 2014;Mwazo et al, 2017). This positions communication as a unique predictor to QSD (Musenze et al, 2013;Mwazo et al, 2017).…”
Section: Internal Control and Quality Service Delivery In Organizationsmentioning
confidence: 99%
“…Similarly, P-C-P model allocates divergent intensity to the quality service measurements. Therefore, to assess service quality, judgments of all measurements of the service: input, processes and outputs should be put into consideration (Musenze et al, 2014).…”
Section: Service Qualitymentioning
confidence: 99%
“…When an organization has a flexible organizational structure, the decision-making process is not complex thus issues are resolved within the shortest time possible. Musenze and Balunywa (2018), did a study on how service delivery was affected by top management support in Nairobi City County Government in Kenya and concluded that the management structure should be well defined with clear guidelines on the responsibilities and roles under each position and should be flexible enough to accommodate most if not all forms of amendments that arise with time.…”
Section: Management Structure and Quality Service Deliverymentioning
confidence: 99%
“…This shows that the participants are still dissatisfied with the services and teaching that have been provided by STIP Marunda Jakarta. Therefore, the leadership of STIP Marunda Jakarta needs to improve the quality of service quality orientated towards service user satisfaction (Doh, 2017;Khan & Su, 2003;Kyriacou & Roca-Sagalés, 2019;Musenze et al, 2014;Ren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%